Pharmacokinetics and biodistribution of a human monoclonal antibody to oxidized LDL in cynomolgus monkey using PET imaging. - Amrita V Kamath; Simon P Williams; Sherry Bullens; Kyra J Cowan; Yvonne Stenberg; Simon R Cherry; Stephen Rendig; David L Kukis; Chris Griesemer; Lisa A Damico-Beyer; Stuart Bunting (PLoS ONE, 2012)
Oxidized low-density lipoprotein (LDL) plays an essential role in the pathogenesis of atherosclerosis. The purpose of this study was to characterize the pharmacokinetics (PK) of a human recombinant IgG1 antibody to oxidized LDL (anti-oxLDL) in cynomolgus monkey. The tissue biodistribution of anti-oxLDL was also investigated using positron emission tomography (PET) imaging.Anti-oxLDL was conjugated with the N-hydroxysuccinimide ester of DOTA (1,4,7,10-tetraazacyclododecane 1,4,7,10-tetraacetic acid) and radiolabeled by chelation of radioactive copper-64 ((64)Cu) for detection by PET. Anti-oxLDL was administered as a single intravenous (IV) dose of 10 mg/kg (as a mixture of radiolabeled and non-labeled material) to two male and two female cynomolgus monkeys. Serum samples were collected over 29 days. Two ELISA methods were used to measure serum concentrations of anti-oxLDL; Assay A was a ligand binding assay that measured free anti-oxLDL (unbound and partially bound forms) and Assay B measured total anti-oxLDL. The biodistribution was observed over a 48-hour period following dose administration using PET imaging.Anti-oxLDL serum concentration-time profiles showed a biphasic elimination pattern that could be best described by a two-compartment elimination model. The serum concentrations obtained using the two ELISA methods were comparable. Clearance values ranged from 8 to 17 ml/day/kg, while beta half-life ranged from 8 to 12 days. The initial volume of distribution and volume of distribution at steady state were approximately 55 mL/kg and 150 mL/kg, respectively. PET imaging showed distribution predominantly to the blood pool, visible as the heart and great vessels in the trunk and limbs, plus diffuse signals in the liver, kidney, spleen, and bone marrow.The clearance of anti-oxLDL is slightly higher than typical IgG1 antibodies in cynomolgus monkeys. The biodistribution pattern appears to be consistent with an antibody that has no large, rapid antigen sink outside the blood space.